The administrative secretary : resource - Anderson, Ruth I. (New York : Gregg Division, McGraw-Hill, 1970)
Contains a number of secretarial techniques and procedures, management principles and theories, and general office reference facts.
Includes bibliographical reference and index
eej 15/01/2019
Loans
Keywords: Secretaries; Office practice